2018
DOI: 10.1186/s13052-018-0531-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of mothers and grandmothers physical and mental health and functioning within 6 months after child NICU/PICU death

Abstract: BackgroundLosing a child is devastating for parents and grandparents. Family and friends generally focus on comforting and supporting the bereaved parents, unintentionally ignoring the bereaved grandparents. Grandmothers and grandfathers often struggle with wanting to help their adult children (deceased child’s parents) without usurping the parents’ responsibilities and decisions regarding the deceased child. Research on mothers’ and grandmothers’ health at about the same time after the same child’s death in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…38 Depression is commonly reported among parents experiencing child loss. [9][10][11][12] In our study, mothers had greater symptoms of depression than fathers consistent with prior research on parental bereavement 9,10 and higher prevalence of major depressive episodes in women compared with men in the general U.S. population. 38 Greater symptoms of depression were also seen in parents of children that died at an older age.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…38 Depression is commonly reported among parents experiencing child loss. [9][10][11][12] In our study, mothers had greater symptoms of depression than fathers consistent with prior research on parental bereavement 9,10 and higher prevalence of major depressive episodes in women compared with men in the general U.S. population. 38 Greater symptoms of depression were also seen in parents of children that died at an older age.…”
Section: Discussionsupporting
confidence: 89%
“…[16][17][18][19] Similar to prior work, bereaved parents in our study experienced substantial adverse mental health symptoms including symptoms of complicated grief, depression, and post-traumatic stress. 6,7,[9][10][11][12] Parents with stronger therapeutic alliances with PICU physi-cians demonstrated less symptoms of complicated grief during bereavement; however, therapeutic alliance was not significantly associated with lesser symptoms of depression, post-traumatic stress, or better overall health.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perinatal death and grief not only affect the nuclear family but also the extended family and the parents' social environment [70]. Grandparents' expectations and hopes for the arrival of a new grandchild are jeopardized, which could have consequences that need to be addressed and understood [71,72]. Grandparents and close family members play a crucial role in social support and communication with parents [73].…”
Section: Discussionmentioning
confidence: 99%
“…Parents face psychological distress in perinatal and neonatal death with an increased risk of post-traumatic stress disorder, depression, and anxiety. Reports have identified the relationship between perinatal death and the devastating impact on parents, including stress and mental health issues lasting for at least 6 months after the death of their infant (44,45). During our parent consultation round to discuss our study protocol, parents indicated that they did not want a 6 months follow-up survey.…”
Section: Discussionmentioning
confidence: 99%